Evaluation of accuracy and performance of a novel, fully gantry integrated 3D laser system for computed tomography guided needle placement: a phantom study - Weigel, Katharina Sophia; Kubik-Huch, Rahel A.; Baer-Beck, Matthias; Canstein, Christian; Kostrzewa, Michael (Diagnostics, 2023)
The purpose of this phantom study was to compare the accuracy, speed and technical performance of CT guided needle placement using a conventional technique versus a novel, gantry integrated laser guidance system for both an expert and a novice. A total of 80 needle placements were performed in an abdominal phantom using conventional CT guidance and a laser guidance system. Analysis of pooled results of expert and novice showed a significant reduction of time (277 vs. 204 s, p = 0.001) and of the number of needle corrections (3.28 vs. 1.58, p < 0.001) required when using laser guidance versus conventional technique. No significant improvement in absolute (3.81 vs. 3.41 mm, p = 0.213) or angular deviation (2.85 vs. 2.18°, p = 0.079) was found. With either approach, the expert was significantly faster (conventional guidance: 207 s vs. 346 s, p < 0.001; laser guidance: 144 s vs. 264 s, p < 0.001) and required fewer needle corrections (conventional guidance: 4 vs. 3, p = 0.027; laser guidance: 2 vs. 1, p = 0.001) than the novice. The laser guidance system helped both the expert and the novice to perform CT guided interventions in a phantom faster and with fewer needle corrections compared to the conventional technique, while achieving similar accuracy.
Gesehen am 19.08.2024